DIPLOMASI INDONESIA TERHADAP UNESCO DALAM MERESMIKAN SUBAK SEBAGAI WARISAN BUDAYA DUNIA - Randa. J, Gusti; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is about Indonesia diplomacy effort to UNESCO to inaugurate Subak in Bali as a world cultural heritage from Indonesia in 2012. Subak Bali is a cultural heritage, it is an irrigation system that regulates the division of water management based on the mindset of harmony and togetherness, it based on formal rules and religious values. Many claims by other countries that take Indonesian culture, such as batik claiming by Malaysia, its make Indonesian government ask to UNESCO to recognize Subak as Indonesian culture. Many participants help the government to get the legally, itâs come from local community and also the government. Subak get legally as a Indonesia heritage culture after 10 years by some process like selection, filtration and fit and proper test. This research applies realist perspective, where it focuses on state as the main actor in international politics. Indonesia wants show to the world that Indonesia also has a heritage culture. To explain this research, the author used theory of diplomacy. This research is a qualitative descriptive research. It uses the library method by taking the data from books, journals, articles, internet and other source. The author visit Department Cultural of Bali to direct research. The result of this research indicate that Indonesian government did multi-track diplomacy effort to get legally Subak as a world cultural heritage of Indonesia from UNESCO on 2012. The effort get a feedback from UNESCO on Mei 2012, when the Bali Heritage culture âThe Cultural Landscape of Bali : Subak System as a Manifestation of The Tri Hita Karanaâ was approved to be a World Cultural heritage. It assigned in the 36th session of UNESCO in St. Petersbug, Russia on 29 June 2012. Keywords: subak, UNESCO, cultural heritage of bali, multy-track diplomacy